1995
DOI: 10.1016/s0022-5223(95)70313-6
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular dysfunction after myocardial ischemia

Abstract: Endothelium-mediated relaxation and smooth muscle function in large coronary arteries are resistant to prolonged global ischemia. We used a small-vessel myograph to test the hypothesis that small intramyocardial artery endothelium and smooth muscle function have greater sensitivity to ischemic injury than large artery endothelium and smooth muscle. Normothermic global ischemia was induced in 15 porcine hearts. Intramyocardial arterial ring segments were assessed at 0, 30, 60, 90, and 120 minutes of ischemia in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Cellular and interstitial edema were also noted. Dignan et al [6] confirmed these observations in studies of ischemia in the porcine heart. Ischemia for less than 30 min did not have a significant effect on the small vessels.…”
Section: Local Structural Changesmentioning
confidence: 75%
“…Cellular and interstitial edema were also noted. Dignan et al [6] confirmed these observations in studies of ischemia in the porcine heart. Ischemia for less than 30 min did not have a significant effect on the small vessels.…”
Section: Local Structural Changesmentioning
confidence: 75%
“…In the present study, we focused our investigation on ischemia, although some kind of reperfusion injury is inevitable in the experiments. As reported by Dignan and colleagues, 4 in vascular studies, separating the effect of ischemia and reperfusion is a necessary step for understanding the pathologic process of the complex I-R injury. The effect of reperfusion on BK Ca , however, awaits further study.…”
Section: Discussionmentioning
confidence: 97%
“…To strictly mimic clinical ischemic conditions, the hearts were maintained in a small amount of Krebs solution to prevent desiccation and sealed with an air-tight plastic bag for 1 hour at room temperature. 4 In both groups, after exposure either to normoxia or ischemia for 1 hour, segments of the left anterior descending coronary artery (for electrophysiologic studies) or the major branches of the artery (diameter 800 to 1,000 m, for isometric force studies) were dissected out.…”
Section: Preparation Of Porcine Coronary Arteries In Ischemic/normoximentioning
confidence: 99%
“…The 2 fundamental mechanisms for the loss of NO bioactivity are reduced synthesis and increased oxidative inactivation by reactive oxygen intermediates, leading to the "no-reflow phenomenon" seen during I/R and, as a consequence, to post-ischemic myocardial dysfunction. 6 Providing supplemental L-arginine to individuals with inadequate NO has been suggested as a rational approach to increase NO production by the endothelium.…”
mentioning
confidence: 99%